Deriving Bisimulation Congruences: 2-Categories vs. Precategories - Sassone, Vladimiro; Sobocinski, Pawel (BRICS Report Series, 2003)
G-relative pushouts (GRPOs) have recently been proposed by the authors as a new foundation for Leifer and Milner's approach to deriving labelled bisimulation congruences from reduction systems. This paper develops the theory of GRPOs further, arguing that they provide a simple and powerful basis towards a comprehensive solution. As an example, we construct GRPOs in a category of `bunches and wirings.' We then examine the approach based on Milner's precategories and Leifer's functorial reactive systems, and show that it can be recast in a much simpler way into the 2-categorical theory of GRPOs.